Spatial variability of eight hazardous heavy metals in agricultural topsoils: a case study from Xuzhou area, Jiangsu, China. Issue 1 (1st January 2021) - Xu, Lei; Zhao, Yulin; Wang, Min; Jiang, Yuanyuan
ABSTRACT: Understanding the concentration of agricultural topsoil heavy metals and their spatial variability is crucial in terms of keeping a close track of the quality of regional environment. In this study, a total of 139 sites were sampled from the agricultural topsoils in Xuzhou area, Jiangsu, China. The contents of eight hazardous heavy metals (Cu, Zn, Ni, Pb, Cr, Hg, As, Cd) were measured for each soil sample. We used semivariogram to study the spatial patterns of these heavy metals, and obtained their spatial distribution maps in Xuzhou area. The descriptive statistics and the correlation between each heavy metal were examined. Our data show that the concentrations of all eight hazardous heavy metals do not exceed the threshold values that are recommended in the national soil quality standard (GB15618–2018). These new results provide a useful basis for the policy design regarding the agriculture, industry, topsoil contamination treatment, and regional environment in this region.